Development and Application of a Mechanistic Population Modeling Approach to Describe Abemaciclib Pharmacokinetics. (13th August 2020) - Chigutsa, Emmanuel; Kambhampati, Siva Rama Prasad; Karen Sykes, Amanda; Posada, Maria M.; van der Walt, Jan‐Stefan; Turner, P. Kellie
Abstract : Abemaciclib is an oral anticancer drug that inhibits cyclin dependent kinases 4 and 6 and is metabolized by cytochrome P450 3A in the intestines and liver to active metabolites. The objectives were (1) to develop a mechanistic model to characterize the pharmacokinetics (PK) of the active moieties and investigate the effect of patient factors and (2) apply the model to dat from two phase III breast cancer trials of abemaciclib in combination with endocrine therapy. To develop the model, data from seven phase I studies and two phase II studies including 421 patients with cancer and 65 healthy individuals were pooled for nonlinear mixed effects modeling. The PK was similar between patients and healthy subjects, and the effects of diarrhea, formulation, race, and patient covariates on exposure were negligible. Application of the model confirmed its predictive performance and that abemaciclib PK did not change when coadministered with endocrine therapy.